2020 IEEE Symposium Series on Computational Intelligence (SSCI) 2020
DOI: 10.1109/ssci47803.2020.9308407
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Optimal Annealing Schedule in Quantum Annealing

Abstract: In many real-life situations in engineering (and in other disciplines), we need to solve an optimization problem: we want an optimal design, we want an optimal control, etc. One of the main problems in optimization is avoiding local maxima (or minima). One of the techniques that helps with solving this problem is annealing: whenever we find ourselves in a possibly local maximum, we jump out with some probability and continue search for the true optimum. A natural way to organize such a probabilistic perturbati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…For large g, which we define for all protocols as g ≡ τ a /τ I , the excitation number decays as a power law. For any g and N , our analytically solvable model (Protocol 1) always outperforms the other protocols, although all of them show scaling similar to 1/g for large g. In numerous other tests (not shown), we found that all non-powerlaw schedules, e.g., with g(t) decaying exponentially, had much worse performance for the same values of τ I , τ a , and T , in agreement with [22]. Figure 3 also shows the data that we used to extrapolate the results to larger N .…”
Section: Effectiveness Of the Solvable Protocol In The Limit Of Maxim...supporting
confidence: 78%
See 2 more Smart Citations
“…For large g, which we define for all protocols as g ≡ τ a /τ I , the excitation number decays as a power law. For any g and N , our analytically solvable model (Protocol 1) always outperforms the other protocols, although all of them show scaling similar to 1/g for large g. In numerous other tests (not shown), we found that all non-powerlaw schedules, e.g., with g(t) decaying exponentially, had much worse performance for the same values of τ I , τ a , and T , in agreement with [22]. Figure 3 also shows the data that we used to extrapolate the results to larger N .…”
Section: Effectiveness Of the Solvable Protocol In The Limit Of Maxim...supporting
confidence: 78%
“…If a protocol is optimal, i.e., outperforms all other protocols at some imposed conditions on the QA schedule and for a certain class of H I , it must remain optimal after time-rescaling, t → λt, in the Schrödinger equation, because the latter merely means the change of timecounting procedure. It has been recently proved [22] that if such a protocol exists, it must correspond to a powerlaw decay of the coupling: g(t) ∼ t a . We will use this result because it strongly restricts the class of the schedules that should be tested in order to prove the optimality.…”
Section: Characteristic Annealing Timesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that empirically, the following two schedules work best: power law and exponential ones [7], [22], [23]. In this section, following [14], we describe the method and corresponding schedules in some detail, and prove that these two schedules are indeed optimal (in some reasonable sense).…”
Section: Optimization: Quantum Annealing Schedules Are Optimal a Quan...mentioning
confidence: 94%
“…In this paper, we summarize results of several papers of ours in which optimality was proven for specific empirically effective quantum algorithms. From this viewpoint, this paper can be viewed as an extended version of several of our previous published papers, in particular, our quantum annealing paper [14].…”
Section: Quantum Algorithm: Remaining Challenges and What We Cover In...mentioning
confidence: 99%